Applying Data Envelopment Analysis to Improve Performance of Emergency Departments in Iranian Hospital: A Case Study - Jelodar, Milad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
One of the most important parts of the health system in each society is hospitals. It should not be forgotten that the emergency room of a hospital is the first point of entry for patients and their companions with the medical system, and one of the problems that often affect the performance of the emergency department is the length of time patients wait in the emergency room. This dissertation has been conducted with the aim of reducing the average waiting time of patients in the emergency department, improving the efficiency of nurses, and increasing the performance of the emergency department. The case study was “Razi Hospital” located in Ahwaz, Iran. It is a general hospital wich at present, with an area of 7,971 square meters, medical services including general surgery, orthopedics 1 and 2, internal medicine, infectious diseases, obstetrics, neonatology, CCU, ICU, emergency department, operating room, physiotherapy, radiology, laboratory, dialysis, echocardiography and specialized clinics visit patients. The data were prepared from the emergency department of the hospital for 12 months in 2018, 2019, and 2020. Data analysis obtained in this study is performed using PIM-DEA software based on the CCR model as a method that is one of the techniques of data envelopment analysis. According to the results, the most important priority is the number of patients with CPR procedures. With this in mind, we can focus on accepting patients with CPR in order to increase the level of emergency function. The next most important factor is the average time the patient leaves the hospital. According to the hospital experts, the time of the patient's discharge from the hospital is a very important indicator, because according to the capacity of the hospital and the number of staff, the lower the average time of the patient's discharge from the emergency room, the better iv the emergency performance. Keywords: Cardiopulmonary Resuscitation as CPR, CCR Model, Data Envelopment Analysis as DEA, Emergency Department

Öz: Her toplumda sağlık sisteminin en önemli parçalarından biri hastanelerdir. Unutulmamalıdır ki, bir hastanenin acil odası, hastalar ve refakatçileri için tıbbi sisteme ilk giriş noktasıdır ve acil servisin performansını sıklıkla etkileyen sorunlardan biri de hastaların bekleme sürelerinin uzunluğudur. acil servis. Bu tez, acil serviste hastaların ortalama bekleme sürelerinin kısaltılması, hemşirelerin verimliliğinin artırılması ve acil servisin performansının artırılması amacıyla yapılmıştır. Örnek olay İran'ın Ahvaz kentinde bulunan "Razi Hastanesi" idi. Şu anda 7,971 metrekare alana sahip, genel cerrahi, ortopedi 1 ve 2 dahil tıbbi hizmetler, dahiliye, enfeksiyon hastalıkları, obstetrik, neonatoloji, CCU, YBÜ, acil servis, ameliyathane, fizyoterapi, radyoloji, laboratuvar, diyaliz, ekokardiyografi ve özel klinikler hastaları ziyaret eder. Veriler 2018, 2019 ve 2020 yıllarında hastanenin acil servisinden 12 ay süreyle hazırlanmıştır. Bu çalışmada elde edilen veri analizi, aşağıdaki tekniklerden biri olan CCR modeline dayalı olarak PIM-DEA yazılımı kullanılarak yapılmıştır. veri zarflama analizi. Sonuçlara göre en önemli öncelik CPR işlemi uygulanan hasta sayısıdır. Bunu akılda tutarak, acil durum işlevinin seviyesini artırmak için CPR'li hastaları kabul etmeye odaklanabiliriz. Bir sonraki en önemli faktör, hastanın hastaneden ortalama ayrılma süresidir. Hastane uzmanlarına göre hastanın hastaneden taburcu süresi çok önemli bir göstergedir çünkü hastanenin kapasitesi ve personel sayısına göre hastanın acil servisten ortalama taburcu olma süresi ne kadar düşükse acil durum performansını iyileştirir. Anahtar Kelimeler: CPR Olarak Kardiyopulmoner Resüsitasyon, CCR Modeli, DEA olarak Veri Zarflama Analizi, Acil Servis
Master of Science in Industrial Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Industrial Engineering, 2021. Supervisor: Assist. Prof. Dr. Sahand Daneshvar.
Keywords: Industrial productivity-Health Sector-Hospitals-Iran; Cardiopulmonary Resuscitation as CPR; CCR Mode; Data Envelopment Analysis as DEA; Emergency Department; Industrial Engineering